AN ANALYSIS OF AL-GHAZALI’S THOUGHT ON HAPPINESS THROUGH HIS BOOK: THE ALCHEMY OF HAPPINESS - Jalili, Ismail; Ulfa, Fadillah (Psikis : Jurnal Psikologi Islami, 2023)
Scholars from many fields have written about happiness and how to achieve it. But this is still an exciting topic, because happiness is one of the most important things people need. This article aimed to examine the significant of happiness for every Muslim in the light of al-Ghazali’s thought through his book al-Chemy of Happiness. The article employs the qualitative approach by using the content analysis method to explore the ideas of al-Ghazali on happiness, its element and its significance for Muslims' lives. The result shows that Ghazali's thoughts on happiness enlighten the Muslims to step on to live happily and be full of salvation. More than that, it becomes one of the psycho-spiritual methods that Muslim and global communities can utilize to live better in the world and hereafter.